Study of ZnO thin film on silicon substrate by sol-gel spin coating method for bio-medical application - Foo, Kai Loong; Mohammad, Kashif; Uda, Hashim, Prof. Dr.; Syed Muhammad Usman, Ali Shah, Dr.; Willander, M., Prof. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/